Desertion : Trust and Mistrust in Civil Wars - McLauchlin, Theodore (Book collections on Project MUSE., 2020)
"Delving deeply into the Spanish Civil War, as well as the civil war in Syria, this book examines the world of combatants in military units, with their comrades and commanders and argues that bonds of trust among combatants keep them fighting, that mistrust pushes them to leave, and that beliefs about political commitments and the motivation to fight shape both"--